A high entropy MAX phase absorbing material and preparation method thereof

By designing high-entropy MAX phase absorbing materials, using the sintering and grinding of elemental powders, the preparation of high-entropy alloys is realized, solving the problem of MAX phase performance regulation in the prior art, and obtaining efficient electromagnetic absorption performance and low-cost Production plan.

CN114744415BActive Publication Date: 2025-01-07SHANDONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210360867.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-07
Publication Date
2025-01-07
Estimated Expiration
2042-04-07

AI Technical Summary

Technical Problem

There is a lack of research and reporting on high-entropy MAX phase components and electromagnetic absorption properties in the prior art, and it is difficult to effectively regulate the performance of MAX phase materials.

Method used

By designing high-entropy MAX absorbing materials with M-position and/or A-position elements, using elemental powder as raw materials, high-entropy alloys with hexagonal crystal structure are prepared through sintering and grinding, to achieve the control of the absorbing performance of the material .

Benefits of technology

The obtained high-entropy MAX phase absorbing material has high purity, strong absorbing ability and wide-band absorption performance, with a minimum reflection loss of no more than -46.36dB, a maximum absorption bandwidth of no less than 3.8GHz, and a simple preparation process and production efficiency. High, low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114744415B_ABST
    Figure CN114744415B_ABST
Patent Text Reader

Abstract

The present invention provides a high entropy MAX phase absorbing material and a preparation method thereof, belonging to the technical field of absorbing material preparation. The nominal molecular formula of the high entropy MAX phase absorbing material is M n+1 AX n , wherein M is at least four elements selected from the group consisting of IIIB, IVB, VB and VIB elements, A is at least one selected from the group consisting of IIIA, IVA, VA and VIA elements, X is carbon, and n is 1, 2 or 3. The ratio of elements in the same position can be regulated according to actual needs. The high entropy MAX phase absorbing material of the present invention has the characteristics of high purity, good absorbing performance and wide absorption bandwidth, and has excellent application prospects in the field of absorbing materials. At the same time, the powder metallurgy method adopted by the present invention has a simple process and high production efficiency, which not only solves the problem of mass production, but also has low energy consumption and low production cost, and therefore has good practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparing absorbing materials, and in particular relates to a high entropy MAX phase absorbing material and a preparation method thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] While the development of communication technology has brought great convenience to people's lives, the impact of electromagnetic radiation has also become increasingly greater, causing great harm to people's health and the natural environment. Therefore, it is of great significance to study new absorbing materials to cope with complex electromagnetic environments. While reducing the pollution of electromagnetic radiation, absorbing materials are also widely used in a variety of civil and military fields, such as radar stealth materials, microwave darkrooms, electromagnetic wave attenuation components and wearable devices. Therefore, absorbing materials are one of the important materials in the technical fields of electromagnetic radiation protection, electromagnetic interference protection, electromagnetic information leakage protection, military stealth, etc.

[0004] MAX phase is a nano-layered ternary compound with diverse structures and properties. It has a hexagonal symmetric structure (P63 / mmc) and has n+1 AX n The molecular formula is . Where M is a transition metal, A is an element of group IIIA, IVA, VA or VIA, X is a C or N atom, and the value of n can be 1, 2, 3 or 4. Since the MAX phase has three chemical bonds, namely covalent, ionic and metallic, the MAX phase often has the good ductility and machinability, thermal conductivity and electrical conductivity, relative flexibility and excellent damage tolerance of metals, as well as the high melting point, high temperature oxidation resistance, good high temperature stability and thermal shock resistance of ceramics.

[0005] In the field of electromagnetic wave absorption, a large number of scholars have explored the absorbing ability of MAX phases. Studies have found that MAX phases often have excellent absorbing properties, such as Ti 2 SiC 2 Cr 2AlC, etc. Changing the component structure of the material by element doping is of great significance for regulating the performance of the MAX phase material system. In recent years, high entropy ceramics have attracted widespread attention because they can improve material properties by designing multi-principal solid solutions with rich components. MAX phase materials have rich chemical diversity, and multi-component solid solutions of MAX phases can be obtained through the M position, A position and / or X position, which is conducive to large-scale control of their properties by the addition of different elements, and therefore has good performance regulation space. However, the inventors found that there is currently no research or report on the high entropy MAX phase composition and electromagnetic absorption performance. Summary of the invention

[0006] In order to overcome the above technical problems, the present invention provides a high entropy MAX phase absorbing material with a combination of M-position and / or A-position elements. The present invention uses element powder as raw material and achieves the absorbing performance of the material through the blending technology of each element in the formula. At the same time, the preparation process is simple and the operation process is flexible, which has good practical application value.

[0007] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:

[0008] In a first aspect of the present invention, a high entropy MAX phase absorbing material is provided, wherein the nominal molecular formula of the high entropy MAX phase absorbing material is M n+1 AX n ;

[0009] wherein M is at least four elements selected from Group IIIB, IVB, VB and VIB elements;

[0010] A is at least one element selected from the group consisting of IIIA, IVA, VA and VIA group elements;

[0011] X is a carbon element, and n is any positive integer from 1 to 3.

[0012] It should be noted that the high entropy MAX phase absorbing material of the present invention, wherein the ratio of elements in the same position can be adjusted according to actual needs, has a hexagonal crystal structure, and the unit cell is composed of M n+1 X n The units and A-layer atoms are stacked alternately in the c direction, and a high-entropy alloy is formed by designing a combination of more than four elements at the M position.

[0013] The second aspect of the present invention provides a method for preparing the above-mentioned high entropy MAX phase absorbing material, the method comprising:

[0014] S1. Determine the required amount of powder containing each element according to the stoichiometric ratio of each element in the nominal chemical formula of the high entropy MAX phase absorbing material, the powder including M single substance powder, A single substance powder and carbon powder;

[0015] S2, mixing the M single substance powder and carbon powder in step S1 and then sintering them;

[0016] S3, mixing the sintered product obtained in step S2 with the A elemental powder and then sintering.

[0017] In another specific embodiment of the present invention, the preparation method further comprises grinding or ball milling the product (loose block) obtained after sintering in step S3 to obtain the high entropy MAX phase absorbing material.

[0018] The third aspect of the present invention provides the application of the above-mentioned high entropy MAX phase absorbing material in the field of electromagnetic radiation.

[0019] Specifically, the applications include but are not limited to radar stealth materials, microwave darkrooms, electromagnetic wave attenuation components and wearable devices.

[0020] The beneficial technical effects of one or more of the above technical solutions are:

[0021] 1) The above technical solution uses element powder as raw material, and realizes the wave absorption performance of the material through the mixing technology of each element in the formula. The obtained high entropy MAX phase wave absorbing material has the advantages of high purity, strong wave absorption ability and wide absorption bandwidth. Analysis shows that the minimum reflection loss of the prepared high entropy MAX phase wave absorbing material is not higher than -46.36dB; the maximum absorption bandwidth is not less than 3.8GHz;

[0022] 2) The preparation method provided by the above technical solution adopts the powder metallurgy method, which has a simple process and high production efficiency. It not only solves the problem of mass production, but also has low energy consumption and low production cost, so it has good practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0024] Figure 1 The X-ray diffraction pattern of the high entropy MAX phase absorbing material prepared in Example 1 of the present invention;

[0025] Figure 2 The scanning electron microscope photo and atomic distribution map of the high entropy MAX phase absorbing material prepared in Example 1 of the present invention; wherein (a) is a scanning electron microscope photo, and (b)-(h) are atomic distribution maps of Mo, Cr, Nb, Ti, V, Al and O respectively;

[0026] Figure 3The transmission electron microscope photo and electron diffraction spectrum of the high entropy MAX phase absorbing material prepared in Example 1 of the present invention; wherein (a) is a HRTEM photo, and (b) is an electron diffraction spectrum;

[0027] Figure 4 The X-ray diffraction pattern of the high entropy MAX phase absorbing material prepared in Example 2 of the present invention;

[0028] Figure 5 This is a scanning electron microscope photograph of the high entropy MAX phase absorbing material prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0029] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0030] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components and / or combinations thereof. It should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention.

[0031] As mentioned above, there is currently no research or report on the high-entropy MAX phase composition and electromagnetic absorption performance.

[0032] In view of this, the present invention proposes a high-entropy MAX phase absorbing material of a combination of M-position and / or A-position elements, and provides a design concept and preparation method of a new high-entropy MAX phase absorbing material based on the development of the existing material system. The preparation method has the characteristics of abundant raw material sources, simple process and flexible operation process.

[0033] Specifically, in a typical embodiment of the present invention, a high entropy MAX phase absorbing material is provided, wherein the nominal molecular formula of the high entropy MAX phase absorbing material is M n+1 AX n ;

[0034] wherein M is at least four elements selected from Group IIIB, IVB, VB and VIB elements;

[0035] A is at least one element selected from the group consisting of IIIA, IVA, VA and VIA group elements;

[0036] X is a carbon element, and n is any positive integer from 1 to 3.

[0037] It should be noted that the high entropy MAX phase absorbing material of the present invention, wherein the ratio of elements in the same position can be adjusted according to actual needs, has a hexagonal crystal structure, and the unit cell is composed of M n+1 X n The units are stacked alternately with the A-layer atoms in the c-direction, and a high-entropy alloy is formed by designing a combination of four or more elements at the M-position.

[0038] In another specific embodiment of the present invention, the M is at least any four elements selected from molybdenum, titanium, vanadium, chromium, niobium, hafnium and tantalum, such as any four elements or five elements.

[0039] In another specific embodiment of the present invention, the molar ratio of the four elements in M ​​can be 0.1-1:0.1-1:0.1-1:0.1-1; preferably 1:1:1:1.

[0040] In another specific embodiment of the present invention, the molar ratio of the five elements in M ​​can be 0.1-1:0.1-1:0.1-1:0.1-1:0.1-1; preferably 1:1:1:1:1.

[0041] The A is at least one element selected from the group consisting of aluminum, germanium, silicon, tin and sulfur.

[0042] In another specific embodiment of the present invention, a method for preparing the above-mentioned high entropy MAX phase absorbing material is provided, the method comprising:

[0043] S1. Determine the required amount of powder containing each element according to the stoichiometric ratio of each element in the nominal chemical formula of the high entropy MAX phase absorbing material, the powder including M single substance powder, A single substance powder and carbon powder;

[0044] S2, mixing the M single substance powder and carbon powder in step S1 and then sintering them;

[0045] S3, mixing the sintered product obtained in step S2 with the A elemental powder and then sintering.

[0046] Wherein, in the step S1,

[0047] The M single substance powder is single substance powder of at least four elements selected from the group consisting of IIIB, IVB, VB and VIB elements;

[0048] A single substance powder is a single substance powder of at least one element selected from the group consisting of IIIA, IVA, VA and VIA elements;

[0049] The molar ratio of the M element, the A element and the carbon element in the required amount of the raw material is (n+1):(1.2-2):(n-0.9-n), wherein n is any positive integer from 1 to 3, i.e., 1, 2 or 3.

[0050] The M is at least any four elements selected from the group consisting of molybdenum, titanium, vanadium, chromium, niobium, hafnium and tantalum.

[0051] In another specific embodiment of the present invention, the molar ratio of the four elements in M ​​can be 0.1-1:0.1-1:0.1-1:0.1-1; preferably 1:1:1:1;

[0052] In another specific embodiment of the present invention, the molar ratio of the five elements in M ​​can be 0.1-1:0.1-1:0.1-1:0.1-1:0.1-1; preferably 1:1:1:1:1.

[0053] In another specific embodiment of the present invention, the A is at least one element selected from the group consisting of aluminum, germanium, silicon, tin and sulfur.

[0054] In another specific embodiment of the present invention, in step S2, in order to facilitate smooth mixing, grinding or ball milling mixing can be used;

[0055] The sintering needs to be carried out in a protective atmosphere (such as argon) or under vacuum conditions. The sintering treatment conditions include: the sintering temperature is controlled at 1200° C. to 1800° C., and the sintering time is 1 to 6 hours.

[0056] In another specific embodiment of the present invention, in step S3, grinding or ball milling can be used to mix smoothly;

[0057] The sintering needs to be carried out in a protective atmosphere (such as argon) or under vacuum conditions. The sintering treatment conditions include: the sintering temperature is controlled at 800° C. to 1600° C., and the sintering time is 0.5 to 3 hours.

[0058] In another specific embodiment of the present invention, the preparation method further comprises grinding or ball milling the product (loose block) obtained after sintering in step S3 to obtain the high entropy MAX phase absorbing material.

[0059] In another specific embodiment of the present invention, application of the above-mentioned high entropy MAX phase absorbing material in the field of electromagnetic radiation is provided.

[0060] In another specific embodiment of the present invention, the applications include but are not limited to radar stealth materials, microwave darkrooms, electromagnetic wave attenuation components and wearable devices.

[0061] The present invention is further explained by the following examples, but they are not intended to limit the present invention. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The test methods for the specific conditions in the following examples are usually carried out under normal conditions.

[0062] Embodiment 1:

[0063] In this embodiment, a high entropy MAX phase absorbing material is prepared. The specific steps are as follows:

[0064] 1) preparing powder according to the molar ratio of Mo:Cr:Nb:Ti:V:Al:C=0.8:0.8:0.8:0.8:0.8:1.9:2.5;

[0065] 2) grinding and mixing the M single substance powder and carbon powder in step 1);

[0066] 3) placing the mixed powder obtained in step 2) in a corundum crucible, heating the mixture to 1600° C. at a rate of 5° C. / min under Ar atmosphere, keeping the temperature for 3 h, and then cooling the mixture in the furnace;

[0067] 4) grinding and mixing the sintered product of step 3) with the A single substance powder;

[0068] 5) The mixed powder obtained in step 4) is transferred to a corundum crucible, and the temperature is raised to 1400° C. at a rate of 5° C. / min under Ar atmosphere, and after being kept at this temperature for 1 hour, the mixture is cooled in the furnace, and the loose block obtained after cooling is taken out and ground to obtain the high entropy MAX phase (Mo) of the present invention. 0.2 Cr 0.2 Nb 0.2 Ti 0.2 V 0.2 ) 4 AlC 3 Wave absorbing material.

[0069] The composition and microstructure of the obtained high entropy MAX phase powder material are respectively Figure 1 , Figure 2 and Figure 3 X-ray diffraction patterns, scanning electron microscope images and transmission electron microscope images are shown.

[0070] The above-mentioned absorbing material was mixed with paraffin in a ratio of 75:25, pressed into a standard ring, and its dielectric constant and magnetic permeability were tested. It was calculated that when the thickness was 1.6 mm, the minimum reflection loss at a frequency of 2 to 18 GHz was -46.36 dB, and the maximum absorption bandwidth was 3.8 GHz when the reflection loss was below -10 dB.

[0071] Embodiment 2:

[0072] In this embodiment, a high entropy MAX phase absorbing material is prepared. The specific steps are as follows:

[0073] 1) preparing powder according to the molar ratio of Mo:Cr:Ti:V:Al:C=1:1:1:1:2:2.1;

[0074] 2) grinding and mixing the M single substance powder and carbon powder in step 1);

[0075] 3) placing the mixed powder obtained in step 2) in a corundum crucible, heating the mixture to 1650° C. at a rate of 5° C. / min under Ar atmosphere, keeping the temperature for 2 h, and then cooling the mixture in the furnace;

[0076] 4) grinding and mixing the sintered product of step 3) with the A single substance powder;

[0077] 5) The mixed powder obtained in step 4) is transferred to a corundum crucible, and the temperature is raised to 1500° C. at a rate of 5° C. / min under Ar atmosphere, and after being kept at this temperature for 1 hour, the mixture is cooled in the furnace, and the loose block obtained after cooling is taken out and ground to obtain the high entropy MAX phase (Mo) of the present invention. 0.25 Cr 0.25 Ti 0.25 V 0.25 ) 4 AlC 3 Wave absorbing material.

[0078] The high entropy MAX phase powder material was obtained, and its composition and microstructure were respectively referred to Figure 4 and Figure 5 X-ray diffraction patterns and scanning electron microscope images are shown.

[0079] The above-mentioned absorbing material was mixed with paraffin in a ratio of 75:25, pressed into a standard ring, and its dielectric constant and magnetic permeability were tested. It was calculated that when the thickness was 1.6 mm, the minimum reflection loss at a frequency of 2 to 18 GHz was -17.78 dB, and the maximum absorption bandwidth was 2.3 GHz when the reflection loss was below -10 dB.

[0080] Embodiment 3:

[0081] In this embodiment, a high entropy MAX phase absorbing material is prepared. The specific steps are as follows:

[0082] 1) preparing powder according to the molar ratio of Mo:Cr:Nb:Ti:V:Al:C=1:1:1:1:1:1.5:2.3;

[0083] 2) grinding and mixing the M single substance powder and carbon powder in step 1);

[0084] 3) placing the mixed powder obtained in step 2) in a corundum crucible, heating the mixture to 1650° C. at a rate of 5° C. / min under Ar atmosphere, keeping the temperature for 3 h, and then cooling the mixture in the furnace;

[0085] 4) grinding and mixing the sintered product of step 3) with the A single substance powder;

[0086] 5) The mixed powder obtained in step 4) is transferred to a corundum crucible, and the temperature is raised to 1300° C. at a rate of 5° C. / min under Ar atmosphere, and after being kept at this temperature for 2 h, the mixture is cooled in the furnace, and the loose block obtained after cooling is taken out and ground to obtain the high entropy MAX phase (Mo) of the present invention. 0.2 Cr 0.2 Nb 0.2 Ti 0.2 V 0.2 ) 4 AlC 3 Wave absorbing material.

[0087] The above-mentioned absorbing material was mixed with paraffin in a ratio of 80:20, pressed into a standard ring, and its dielectric constant and magnetic permeability were tested. It was calculated that when the thickness was 1.0 mm, the minimum reflection loss at a frequency of 2 to 18 GHz was -40.52 dB, and the maximum absorption bandwidth was 2.9 GHz when the reflection loss was below -10 dB.

[0088] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to perform equivalent replacements on parts thereof. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention. Although the above describes the specific implementation methods of the present invention, it is not intended to limit the protection scope of the present invention. Those skilled in the art should understand that, based on the technical solution of the present invention, various modifications or deformations that can be made by those skilled in the art without creative labor are still within the protection scope of the present invention.

Claims

1. A high entropy MAX phase absorbing material, characterized in that: The nominal molecular formula of the high entropy MAX phase absorbing material is M n+ 1AX n ; wherein M is at least four elements selected from Group IIIB, IVB, VB and VIB elements; A is at least one element selected from the group consisting of IIIA, IVA, VA and VIA group elements; X is a carbon element, and n is any positive integer from 1 to 3; M is at least any four elements selected from molybdenum, titanium, vanadium, chromium, niobium, hafnium and tantalum; The molar ratio of the four elements in M ​​is 0.1~1:0.1~1:0.1~1:0.1~1; The molar ratio of the five elements in M ​​is 0.1~1:0.1~1:0.1~1:0.1~1:0.1~1:0.1~1; The preparation method of the high entropy MAX phase absorbing material comprises: S1. Determine the required amount of powder containing each element according to the stoichiometric ratio of each element in the nominal chemical formula of the high entropy MAX phase absorbing material, the powder including M single substance powder, A single substance powder and carbon powder; S2, mixing the M single substance powder and carbon powder in step S1 and then sintering them; S3, mixing the sintered product obtained in step S2 with the A single substance powder and then sintering.

2. The high entropy MAX phase absorbing material according to claim 1, characterized in that: The molar ratio of the four elements in M ​​is 1:1:1:

1.

3. The high entropy MAX phase absorbing material according to claim 1, characterized in that: The molar ratio of the five elements in M ​​is 1:1:1:1:

1.

4. The high entropy MAX phase absorbing material according to claim 1, characterized in that: The A is at least one element selected from the group consisting of aluminum, germanium, silicon, tin and sulfur.

5. The method for preparing the high entropy MAX phase absorbing material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: S1. Determine the required amount of powder containing each element according to the stoichiometric ratio of each element in the nominal chemical formula of the high entropy MAX phase absorbing material, the powder including M single substance powder, A single substance powder and carbon powder; S2, mixing the M single substance powder and carbon powder in step S1 and then sintering them; S3, mixing the sintered product obtained in step S2 with the A elemental powder and performing a sintering treatment; The M is at least any four elements selected from molybdenum, titanium, vanadium, chromium, niobium, hafnium and tantalum; The molar ratio of the four elements in M ​​is 0.1~1:0.1~1:0.1~1:0.1~1; The molar ratio of the five elements in M ​​is 0.1~1:0.1~1:0.1~1:0.1~1:0.1~1:0.1~1; A is at least one element selected from aluminum, germanium, silicon, tin and sulfur; In step S1, the molar ratio of the M element, the A element and the carbon element in the required amount of the raw material is (n+1):(1.2-2):(n-0.9-n), wherein n is any positive integer from 1 to 3, i.e., 1, 2 or 3.

6. The preparation method according to claim 5, characterized in that: The molar ratio of the four elements in M ​​is 1:1:1:

1.

7. The preparation method according to claim 5, characterized in that: The molar ratio of the five elements in M ​​is 1:1:1:1:

1.

8. The preparation method according to claim 5, characterized in that: In the step S2, grinding or ball milling is used for mixing; The sintering is carried out under protective atmosphere or vacuum conditions. The sintering treatment conditions include: the sintering temperature is controlled at 1200° C. to 1800° C., and the sintering time is 1 to 6 hours.

9. The preparation method according to claim 5, characterized in that: In the step S3, grinding or ball milling is used for mixing; The sintering is carried out in a protective atmosphere or under vacuum conditions. The sintering treatment conditions include: the sintering temperature is controlled at 800° C. to 1600° C., and the sintering time is 0.5 to 3 hours.

10. The preparation method according to claim 5, characterized in that: The preparation method further comprises grinding or ball milling the product obtained after sintering in step S3 to obtain the high entropy MAX phase absorbing material.

Citation Information

Patent Citations

  • High-entropy two-dimensional material, high-entropy MAX phase material and preparation methods thereof

    CN112875703A